Gene Therapy in Inherited Retinal Diseases: An Update on Current State of the Art - Amato, Alessia; Arrigo, Alessandro; Aragona, Emanuela; Manitto, Maria Pia; Saladino, Andrea; Bandello, Francesco; Battaglia Parodi, Maurizio (Frontiers in Medicine, 2021)
Background: Gene therapy cannot be yet considered a far perspective, but a tangible therapeutic option in the field of retinal diseases. Although still confined in experimental settings, the preliminary results are promising and provide an overall scenario suggesting that we are not so far from the application of gene therapy in clinical settings. The main aim of this review is to provide a complete and updated overview of the current state of the art and of the future perspectives of gene therapy applied on retinal diseases. Methods: We carefully revised the entire literature to report all the relevant findings related to the experimental procedures and the future scenarios of gene therapy applied in retinal diseases. A clinical background and a detailed description of the genetic features of each retinal disease included are also reported. Results: The current literature strongly support the hope of gene therapy options developed for retinal diseases. Although being considered in advanced stages of investigation for some retinal diseases, such as choroideremia (CHM), retinitis pigmentosa (RP), and Leber's congenital amaurosis (LCA), gene therapy is still quite far from a tangible application in clinical practice for other retinal diseases. Conclusions: Gene therapy is an extremely promising therapeutic tool for retinal diseases. The experimental data reported in this review offer a strong hope that gene therapy will be effectively available in clinical practice in the next years.